Comparative genomic analysis of magnetotactic bacteria from the Deltaproteobacteria provides new insights into magnetite and greigite magnetosome genes required for magnetotaxis. (23rd April 2013) - Lefèvre, Christopher T.; Trubitsyn, Denis; Abreu, Fernanda; Kolinko, Sebastian; Jogler, Christian; de, Luiz Gonzaga Paula; de, Ana Tereza R.; Kube, Michael; Reinhardt, Richard; Lins, Ulysses; Pignol, David; Schüler, Dirk; et al.
Summary Magnetotactic bacteria (MTB) represent a group of diverse motile prokaryotes that biomineralize magnetosomes, the organelles responsible for magnetotaxis. Magnetosomes consist of intracellular, membrane‐bounded, tens‐of‐nanometre‐sized crystals of the magnetic minerals magnetite (Fe3O4) or greigite (Fe3S4) and are usually organized as a chain within the cell acting like a compass needle. Most information regarding the biomineralization processes involved in magnetosome formation comes from studies involving Alphaproteobacteria species which biomineralize cuboctahedral and elongated prismatic crystals of magnetite. Many magnetosome genes, the mam genes, identified in these organisms are conserved in all known MTB. Here we present a comparative genomic analysis of magnetotactic Deltaproteobacteria that synthesize bullet‐shaped crystals of magnetite and/or greigite. We show that in addition to mam genes, there is a conserved set of genes, designated mad genes, specific to the magnetotactic Deltaproteobacteria, some also being present in Candidatus Magnetobacterium bavaricum of the Nitrospirae phylum, but absent in the magnetotactic Alphaproteobacteria. Our results suggest that the number of genes associated with magnetotaxis in magnetotactic Deltaproteobacteria is larger than previously thought. We also demonstrate that the minimum set of mam genes necessary for magnetosome formation in Magnetospirillum is also conserved in magnetite‐producing, magnetotactic Deltaproteobacteria. Some putative novel functions of mad genes are discussed.